Corporate Social Responsibility: Consciousness, Solidarity and Efficiency - Aspíllaga Alayza, Victor (2010)
The author starts from an analysis of the relationship between Law and corporate social responsibility. In this line, the objective of this work is to determine the role of Law that helps the business market generate well-being for all its interest groups. For this, he uses as research tools not only the legislation on the subject, but also the economic perspective. On the one hand, there are guidelines created by the European Commission that generate a debate regarding how to promote CSR in companies. For example, the Green Book that establishes models of CSR actions and presents ideas about how the practice of CSR can be manifested. On the other hand, the author suggests granting tax benefits to the income tax applied to the profits of the company destined for social investment. Following this, an analysis of the internal dimension of the companies, the treatment of workers and shareholders is carried out. On the other hand, he explains the economic reasons for the intervention of the State in the generation of norms through the attribution of entitlements to the agents. Reasons of efficiency, equity and other justice considerations were the examples. Finally, the issue of "non-regulation" of CSR is discussed. This is justified based on the lack of CSR regulation framework. The author considers the creation of an association that could promote the creation of the aforementioned index in the stock market by pointing out and grouping companies that practice CSR. In conclusion, it is argued that there are different ways to promote CSR. The feasibility of each strategy must be evaluated based on the situation with greater efficiency. And for this, in the opinion of the author, a regulation should not necessarily be imposed since the costs of imposing it must be compared with the benefits that it may generate before reaching a conclusion. However, a lower tax burden is pertinent for the percentage of income tax applied to profits earmarked for social investment.